Aripiprazole-induced oculogyric crisis (acute dystonia) - Bhachech, Jyotik T. (Medknow Publications & Media Pvt Ltd, 2012)
Aripiprazole is the third generation atypical antipsychotic and a dopamine serotonin system stabilizer (DSS) effective against positive and negative symptoms of schizophrenia. It has a low propensity for extrapyramidal side effects, causes minimal weight gain or sedation, produces no elevation in serum prolactin levels, and does not cause prolongation of QTc interval. This case report is of a patient suffering from schizophrenia (paranoid). The patient developed oculogyric crisis (acute dystonia) with aripiprazole dose uptitration. Dystonic reaction resolved with promethazine administration. Naranjo's causality assessment reveals probable association of aripiprazole with oculogyric crisis. A thorough workup and vigilance is required prior to initiation of aripiprazole in the case of schizophrenia.